2017
DOI: 10.5935/abc.20170150
|View full text |Cite
|
Sign up to set email alerts
|

First results of the Brazilian Registry of Percutaneous Left Atrial Appendage Closure

Abstract: BackgroundLeft atrial appendage closure (LAAC) is an effective alternative to oral anticoagulation (OA) for the prevention of stroke in patients with non-valvular atrial fibrillation (NVAF).ObjectiveTo present the immediate results and late outcomes of patients submitted to LAAC and included in the Brazilian Registry of Percutaneous Left Atrial Appendage Closure.Methods91 patients with NVAF, high stroke risk (CHA2DS2VASc score = 4.5 ± 1.5) and restrictions to OAC (HAS-BLED score = 3.6 ± 1.0) underwent 92 LAAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…After reading the abstract and partial text of each study, unrelated studies, reviews, case reports, studies with unclear outcomes or incomplete data, and studies in which LAAO was combined with other surgeries were excluded. Finally, 32 studies 13 44 that satisfied the selection criteria were included in this meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After reading the abstract and partial text of each study, unrelated studies, reviews, case reports, studies with unclear outcomes or incomplete data, and studies in which LAAO was combined with other surgeries were excluded. Finally, 32 studies 13 44 that satisfied the selection criteria were included in this meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our procedural success rate was similar to previous studies. [11][12][13] Landmesser et al 12 reported that the procedural success of LAA occlusion with the Amulet device was 99.0% in their multicenter registry, which included 1,088 patients. 12 They reported peri-device leak in 2% of patients during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Two Brazilian registries have been recently published and suggested the safety of appendage occlusion device implantation. Guerios et al, 12 performed a multicenter registry and evaluated the results of 91 patients with nonvalvular AF (62% ineligible for anticoagulation) and high risk of stroke (CHA2DS2VASc 4.5 ± 1.5), submitted to the implantation of 96 prostheses, with the ACP (Amplatzer Cardiac Plug) being implanted in 94.6%. The implant success rate was 97.8%, with 7.2% of complications, with five pericardial effusions requiring pericardiocentesis, one non-dedicated device embolization and one gas embolism without sequelae.…”
Section: Referencesmentioning
confidence: 99%